Comparative genome analysis and genome-guided physiological analysis of Roseobacter litoralis - Kalhoefer, Daniela; Thole, Sebastian; Voget, Sonja; Lehmann, Rüdiger; Liesegang, Heiko; Wollher, Antje; Daniel, Rolf; Simon, Meinhard; Brinkhoff, Thorsten (BMC genomics, 2011)
Roseobacter litoralis OCh149, the type species of the genus, and Roseobacter denitrificans OCh114 were the first described organisms of the Roseobacter clade, an ecologically important group of marine bacteria. Both species were isolated from seaweed and are able to perform aerobic anoxygenic photosynthesis. The genome of R. litoralis OCh149 contains one circular chromosome of 4,505,211 bp and three plasmids of 93,578 bp (pRLO149_94), 83,129 bp (pRLO149_83) and 63,532 bp (pRLO149_63). Of the 4537 genes predicted for R. litoralis, 1122 (24.7%) are not present in the genome of R. denitrificans. Many of the unique genes of R. litoralis are located in genomic islands and on plasmids. On pRLO149_83 several potential heavy metal resistance genes are encoded which are not present in the genome of R. denitrificans. The comparison of the heavy metal tolerance of the two organisms showed an increased zinc tolerance of R. litoralis. In contrast to R. denitrificans, the photosynthesis genes of R. litoralis are plasmid encoded. The activity of the photosynthetic apparatus was confirmed by respiration rate measurements, indicating a growth-phase dependent response to light. Comparative genomics with other members of the Roseobacter clade revealed several genomic regions that were only conserved in the two Roseobacter species. One of those regions encodes a variety of genes that might play a role in host association of the organisms. The catabolism of different carbon and nitrogen sources was predicted from the genome and combined with experimental data. In several cases, e.g. the degradation of some algal osmolytes and sugars, the genome-derived predictions of the metabolic pathways in R. litoralis differed from the phenotype. The genomic differences between the two Roseobacter species are mainly due to lateral gene transfer and genomic rearrangements. Plasmid pRLO149_83 contains predominantly recently acquired genetic material whereas pRLO149_94 was probably translocated from the chromosome. Plasmid pRLO149_63 and one plasmid of R. denitrifcans (pTB2) seem to have a common ancestor and are important for cell envelope biosynthesis. Several new mechanisms of substrate degradation were indicated from the combination of experimental and genomic data. The photosynthetic activity of R. litoralis is probably regulated by nutrient availability.